PENENTUAN STRUKTUR MOLEKUL KOLAGEN SISIK IKAN KAKATUA (Scarus sp) BERDASARKAN SERAPAN MOLEKUL TERHADAP GELOMBANG FTIR (FOURIER-TRANSFORM INFRARED SPECTROSCOPY ANALYSIS) - Shellyn Prastisia Mberato; Inneke F M Rumengan; Veibe Warouw; Stenly Wullur; Natalie D T Rumampuk; Suzanne L Undap; Pipih Suptijah; Aldian Hein Luntungan (Sam Ratulangi University, 2020)
Parrot fish (Scarus sp) is a commodity which commonly consumed in North Sulawesi. High consumption of this fish has caused the high amount of fish scales as wastes. As parrot fish scales contain protein that could be transformed into commercial products such as collagen. Collagen could be applied in the industrial fields including cosmetics and pharmaceutics. The purpose of this study was to determine molecular structure of collagen derived from the wet and dry parrot fish (Scarus sp) scales, based on molecular absorption of electromagnetic in the infrared region of the fourier transform infrared spectroscopy.Preparation of collagen of fish scales both in wet and dry forms, was initially performed with pre-treatment of raw materials by maceration in sodium hydroxide (NaOH) solution for 48 hours. Then hydrolysis process was conducted in hydrochloric acid (HCl) solution again for 48 hours to remove mineral contents of the scales. Collagen yield of fish scales in wet and dry forms was 2.23% and 3.00%, respectively, with pH 7, and the respective water content was 13% and 12%. For collagen derived from the wet scales, the functional groups of amide A and B absorb the electromagnetic at infrared region of 3429 cm-1 and 2930 cm-1), respectively. Also amide I, II and III absorb the electromagnetic at infrared region of 1657 cm-1, 1452 cm-1 and 1242 cm-1, respectively. It was comparable to that of collagen derived from the dry scales, the functional groups of amide A and B absorb the electromagnetic at infrared region of 3425 cm-1 and 2910 cm-1), respectively. Also amide I, II and III absorb the electromagnetic at infrared region of 1653 cm-1, 1402 cm-1 and 1244 cm-1, respectively. The amide III group of the wet scales derived collagen as well as the dry scales derive collagen absorb the electromagnetics at infrared region in the range of 1309-1229 cm-1 indicating that the fish scale derived collagen has not denatured yet, but still in triple helix structure. Molecular functional groups detected for the parrot fish scales derived collagen are in the range of those for collagen standard.Keywords : fish scale, Scarus sp, collagen, molecule structure, proximate AbstrakIkan kakatua (Scarus sp) merupakan salah satu jenis komiditi ikan yang banyak dikonsumsi di Sulawesi Utara. Tingginya konsumsi ikan kakatua berakibat banyaknya limbah kuliner ikan ini berupa sisik ikan. Padahal sisik ikan kakatua mengandung protein yang dapat ditransformasikan menjadi produk samping komersial seperti kolagen. Kolagen dapat diaplikasikan pada bidang industry kosmetik dan farmasika. Tujuan penelitian ini menentukan struktur molekul kolagen dari sisik ikan kakatua (Scarus sp) berdasarkan wilayah serapan gelombang infra red.Preparasi kolagen dari sisik ikan baik dalam bentuk basah maupun kering, diawali dengan proses pre-treatment bahan baku dengan melakukan perendaman menggunakan larutan NaOH selama 48 jam. Selanjutnya adalah tahap hidrolisis yang dilakukan dengan perendaman sampel menggunakan larutan asam klorida (HCl) selama 48 jam untuk menghilangkan mineral yang ada dalam sisik. Kolagen sisik basah dan sisik kering dari ikan kakatua memiliki nilai rendemen masing-masing sebesar 2.23% dan 3.00%, nilai pH 7 serta kadar air sebesar 13% dan 12%. Pada kolagen sisik basah terdeteksi Amida A mempunyai bilangan gel (3429 cm-1), Amida B (2930 cm-1). Amida I (1657 cm-1), Amida II (1452 cm-1 ) dan Amida III (1242 cm-1), sedangkan pada kolagen sisik kering terdeteksi Amida A mempunyai bilangan gel (3425 cm -1 ), Amida B (2910 cm-1 ). Amida I (1653 cm-1 ), Amida II (1402 cm-1 ) dan Amida III (1244 cm-1). Amida III pada kolagen sisik basah dan kolagen sisik kering terdeteksi pada wilayah serapan 1309-1229 cm-1 hal menandakan bahwa kolagen sisik ikan kakatua belum terdenaturasi karena masih terdapat struktur triple helix. Gugus fungsional kolagen sisik kering dan kolagen sisik basah dari ikan kakatua memenuhi standar gugus fungsional kolagen standar.Kata kunci : sisik, Scarus sp, kolagen, gugus fungsi, proksimat